2011
DOI: 10.1080/17441692.2010.551519
|View full text |Cite
|
Sign up to set email alerts
|

Restoring dignity: Social reintegration after obstetric fistula repair in Ukerewe, Tanzania

Abstract: This study explores barriers and facilitating factors women experience re-integrating into society after treatment of an obstetric fistula in rural Tanzania. A total of 71 women were interviewed in the Mwanza region of Tanzania, including a community control group. The majority of the women who received successful surgical repairs reported that, over time, they were able to resume many of the social and economic activities they engaged in prior to the development of a fistula. Familial support facilitated both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
112
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(140 citation statements)
references
References 15 publications
11
112
0
Order By: Relevance
“…Several scholars have demonstrated the importance of family and community support to the reintegration of fistula patients (Diallo, 2009;Mohammad, 2007;Pope et al, 2011). Similarly, in this study, moral support and acceptance from family and the larger community were emphasized.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…Several scholars have demonstrated the importance of family and community support to the reintegration of fistula patients (Diallo, 2009;Mohammad, 2007;Pope et al, 2011). Similarly, in this study, moral support and acceptance from family and the larger community were emphasized.…”
Section: Discussionmentioning
confidence: 91%
“…Thus, it is seen as the first step toward reintegration. For instance, the women with residual symptoms in the Tanzania study perceived themselves as not yet healed and reported a low perception of their quality of life (Pope et al, 2011). The current study did not directly measure quality of life although it points to better social reintegration among women with successful repair in the post-corrective surgery period.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…For instance, Mohammad 26 describes a re-integration programme for fistula survivors in Nigeria, where the need for economic empowerment was given priority, to good effect. Nonetheless, in some studies, for example Pope, Bangser and Requejo, 27 women have been shown to be able to resume normal economic activities, with their families as the core supporting unit.…”
Section: Discussionmentioning
confidence: 99%